Domain structure of epitaxial PZT thin films grown on MgO(001) by RF magnetron sputtering - Lee, KS; Kang, YM; Baik, S (GORDON BREACH SCI PUBL LTD, 1997)
Epitaxial Pb(ZrxTi1-x)O-3 (x=0.0 similar to 0.32) thin-films were successfully grown on MgO(001) single crystal by RF magnetron sputtering. Lattice constants and crystal quality of the films were measured by the X-ray theta-2 theta scan and the FWHM of (001) rocking curves, respectively. Degree of c axis orientation and crystal quality of the films improved gradually with increasing Zr concentration. High temperature X-ray technique was employed to study the domain formation as a function of temperature during cooling from cubic phase to tetragonal phase. The initial values of a at the Curie temperature also increased with increasing Zr concentration.
Keywords: STRAIN RELAXATION; DEPOSITION; MGO(100)